An Analysis of Translation Equivalence in English–Indonesian Agribusiness Terminology: A Case Study at Universitas Timor - Iis Aprianti; Yoni Rahayu; Muhammad Muslim Nasution; Soraya Grabiella Dinamika; Elitaria Bestri Agustina Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the translation equivalence of English agribusiness terminology and its Indonesian equivalents used in the English for Agribusiness learning materials at Universitas Timor. The research employed a descriptive qualitative case study design. The data consisted of fifty English agribusiness terms and their Indonesian translations collected from instructional materials used in the Agribusiness Study Program. The data were analyzed by integrating Baker’s word-level equivalence, Nida’s dynamic equivalence, and Koller’s denotative equivalence to evaluate lexical, conceptual, and communicative correspondence between the source and target languages. The findings revealed that 19 terms (38%) of the terms were categorized as equivalent, while 29 (58%) were classified as partially equivalent, and 2 terms (4%) were classified non-equivalent translations were identified. The equivalent translations successfully preserved the lexical meaning and agribusiness concepts of the source terms, whereas the partially equivalent translations involved lexical additions to improve clarity and naturalness in Indonesian without altering the intended meaning. The study concludes that the English for Agribusiness learning materials at Universitas Timor provide a high level of translation equivalence and effectively support students' comprehension of specialized agribusiness terminology in English for Specific Purposes (ESP). Keywords: Agribusiness Terminology; English for Specific Purposes (ESP); English–Indonesian Translation; Qualitative Study; Translation Equivalence